2013
DOI: 10.1088/0022-3727/46/35/355201
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of positive and negative modes of nanosecond pulsed discharge in water and electrostriction model of initiation

Abstract: This work investigates the development of nanosecond pulsed discharges in water ignited with the application of both positive and negative polarity pulses to submerged pin to plane electrodes. Optical diagnostics are used to study two main aspects of these discharges: the initiation phase, and the development phase. Nanosecond pulses up to with rise time, duration and fall time are used to ignite discharges in a gap between a copper plate and a tungsten needle with radius of curvature of . Fast ICCD imaging is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
59
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 20 publications
8
59
2
2
Order By: Relevance
“…The pulse generating, monitoring and triggering was performed as described in [16, 17]. Briefly, the power supply (FID Tech Company) generated pulses with +15.5 kV pulse amplitude in 50 Ohm coaxial cable (31 kV on the high-voltage electrode due to pulse reflection), 10 ns pulse duration (90% amplitude), 2 ns rise time and 3 ns fall time.…”
Section: Experimental Setup and Methodologymentioning
confidence: 99%
“…The pulse generating, monitoring and triggering was performed as described in [16, 17]. Briefly, the power supply (FID Tech Company) generated pulses with +15.5 kV pulse amplitude in 50 Ohm coaxial cable (31 kV on the high-voltage electrode due to pulse reflection), 10 ns pulse duration (90% amplitude), 2 ns rise time and 3 ns fall time.…”
Section: Experimental Setup and Methodologymentioning
confidence: 99%
“…11 In the case of nanosecond discharges, the formation of a low-density region by an electrostrictive force acting on a dielectric fluid in a non-uniform electric field has been assumed. [31][32][33][34][35] The electrostrictive force induces negative pressure regions in the vicinity of an electrode tip, resulting in the formation of liquid ruptures (or nanopores). 31,32 This electrostriction model is effective in liquid with high dielectric permittivity such as in water and is dominant in a nanosecond time scale of 10 ns, which is much shorter than the characteristic time scale of hydrodynamic processes.…”
mentioning
confidence: 99%
“…1,33,34 Electrons can be accelerated in the ruptures to ionize water molecules, leading to electron avalanche that initially forms a plasma region. 35 In the case of sub-microsecond discharges, it has been proposed that streamer propagation is triggered by field emission at the interface of pre-existing microbubbles, in which electron impact ionization occurs. 36,37 In the case of microsecond or longer pulsed discharges, a bubble theory associated with thermal effects is most likely to be the main mechanism.…”
mentioning
confidence: 99%
“…In a series of papers, Seepersad et al (2013) combine single point to plate, single pulse experiments, observed via ultra-fast photography, with ponderomotive electrostriction theory to understand plasma pre-onset chemistry, particularly the role if any of nano-bubbles in the electrolyte bulk. Sub nanosecond (~400ps), well defined, high voltage (~15-20kV), square pulses are examined singly.…”
Section: Plasma Electrolysis Literaturementioning
confidence: 99%
“…However, the limiting requirement is also set by minimum voltage rise rate (dV/dt) as shown by Seepersad et al (2013). A 100ps rise time is approximately equivalent to a 3.5GHz repetition rate AC signal but includes non-trivial harmonics up to 5x this value at ~18GHz.…”
Section: Short Pulse Generator Technologymentioning
confidence: 99%